Key inflammatory players for infarcted mass and cardiac remodeling after acute myocardial infarction - Fonseca, Francisco A. H.; França, Carolina N.; Fonseca, Henrique A. R.; Serra, Andrey J.; Izar, Maria C. (Frontiers in Cardiovascular Medicine, 2025)
Atherosclerosis has been defined as an inflammatory disease. As observed during acute infections, excess inflammatory activity is associated with disease severity and mortality. After myocardial infarction, several waves of inflammatory cells play a crucial role in infarct size and cardiac remodeling. In the short and long term, subtypes of inflammatory cells and cytokines released orchestrate the healing and stability of coronary disease. In recent years, some anti-inflammatory therapies have been shown to reduce the residual cardiovascular risk. Furthermore, some medications for treating risk factors and adoption of healthy lifestyle have decreased inflammatory markers and cardiovascular outcomes. In this complex network of possibilities, multiple interventions and not just on specific cell type or cytokine may provide better results. Finally, mild or moderate inflammatory activity appears necessary for better recovery and survival after acute myocardial infarction.